Capacidade resistente de vigas celulares mistas à instabilidade no montante de alma - Ferreira, Felipe Piana Vendramell (Universidade Federal de São Carlos, 2021)
The present work aims to investigate the web post buckling resistance of composite cellular beams. For this task, geometrical and physical non-linear analyses are developed in the ABAQUS® software. The computational model was calibrated considering physical models of composite cellular beams, with steel-concrete composite slabs, and steel-concrete composite beams with precast hollow-core slabs. Subsequently, the numerical models were unified to represent the composite cellular beams associated with precast hollow-core slabs. Two parametric studies were carried out, varying the cellular beams key parameters, such as the web-post width and the opening diameter. The first study evaluated the floor systems, considering steel-concrete composite and precast hollow core slabs. The second study investigated the composite action, varying the spacing, with one and two connecting lines, between the shear studs. In the first study, considering the section with double symmetry and precast hollow core slab, the predominant failure mode was web post buckling. For the section with asymmetry, the predominant failure mode was the combination of the plastic mechanism with the web post buckling accompanied (or not) by the shear stud rupture. In the analysis of the type of slab it was found that the composite cellular beams with precast hollow-core slabs presented greater resistance. The results of the first parametric study showed that the resistance of the composite cellular beams was not limited only by the resistance of the cellular profile, but also, of the slab, due to the shear resistance. On the other hand, in the second parametric study, a drop in global shear resistance was observed due to the absence of shear studs above the second opening, close to the support. The numerical models of composite cellular beams with hollow-core slab and concrete topping presented greater global shear resistance than the models without concrete topping. However, for those models with concrete topping, there were a greater number of observations in which the shear studs rupture occurred. Finally, the results of the second study were compared with a proposed equation, which takes into account the global shear resistance due to web post buckling, Vierendeel mechanism and composite action. The proposed analytical model showed an excellent correlation with the results of the numerical analyses, especially for the models in which the combination of the web post buckling with the plastic mechanism was identified.
Web post buckling resistance of composite cellular beams
Keywords: Viga celular mista; Laje alveolar pré-fabricada; Conectores de cisalhamento; Instabilidade no montante de alma; Modelagem numérica; Composite cellular beams; Precast hollow-core slabs; Shear connectors; Web post buckling; Numerical modeling; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS